Characteristics of extreme temperature and precipitation in China in 2017 based on ETCCDI indices - Hong YIN (Advances in Climate Change Research, 2018)
Based on the homogenized daily data in 2419 stations in China from 1961 to 2017, we calculated 26 extreme temperature and precipitation indices as defined by the Expert Team on Climate Change Detection and Indices (ETCCDI), and analyzed the characteristics of extreme temperature and precipitation in China in 2017. For China average, all the high temperature indices were above the 30-year average of 1961–1990 and the extreme low temperature indices are lower than their corresponding 1961–1990 average. The most extreme precipitations in 2017 were within the range of one standard deviation of precipitation change during 1961–2017. The annual minima of daily maximum temperature (TXn) and daily minimum temperature (TNn) reached the recorded highest level, while the number of cold nights (TN10p), cold days (TX10p), and cold spell duration index (CSDI) reached the recorded lowest values. Some indices were ranked at the second or third place since 1961, including annual maxima of daily maximum temperature (TXx) and of daily minimum temperature (TNx), warm nights (TN90p), frost days (FD), icing days (ID), summer days (SU), and growing season length (GSL). Other extreme temperature indices were ranked in the top 10 since 1961. Meanwhile, for the averaged extreme precipitation indices in China, seven out of the 10 extreme precipitation indices in 2017 were located within the range of one standard deviation, indicating a normal situation for extreme precipitation in 2017. Keywords: Climate warming, Extreme temperature, Extreme precipitation, 2017